Propuesta de reforma al art. 159 del código orgánico integral penal incorporando una multa de cinco remuneraciones básicas unificadas a la sanción - Vaca Guerra, Heather Yadira (2017)
Domestic violence generated marital instability, affecting every household member; of course we must consider that domestic abuse can have severe consequences, which generally have physical and emotional medium and long-term sequelae, and also can present with physical or permanent mental disabilities that lead in extreme cases even death. This type of violence brings complications in the social structure, where serious psychological, physical and sexual sequelae are detected. From the point of view of law, it is an answer to this problem working in the legal determination of illicit and increases penalties, which has led to sanction the various modifications of the rules, especially in Criminal Comprehensive Organic Code, also urge the judges to conduct a ruthless application of them. Unfortunately today domestic violence, is considered one of the most important for the commission of crimes causes, especially against those who are the family, regardless of age, sex, color or social status.